Angel heart [videorecording (DVD)] - De Niro, Robert; Parker, Alan, 1944-2020; Rampling, Charlotte, 1946-; Rourke, Mickey; Bonet, Lisa, 1967-; Hjortsberg, William, 1941- (Lions Gate Home Entertainment, 2004)
Harry Angel is hired for to track down the big band singer Johnny Favourite. What seems like a straightforward missing person case dramatically becomes a murder hunt for this down-and-out private detective. His client Louis Cyphre, a mysterious stranger, is forced to up his fee to keep Angel on the case. Each of Angel's leads ends up as a victim of a ritualistic act of murder as he begins to put together the pieces in the jigsaw of Johnnys' strange story ... The nightmare has only just begun.